Perancangan Media Promosi Kesehatan Reproduksi Dalam Pelaksanaan Pik-R (Pusat Informasi Dan Konseling Remaja) Berdasarkan Teori P-Process (Studi Kasus Di Kampung Kb Lontar Kota Surabaya) - Annisa Firdaus Suharto (Dian Nuswantoro Semarang, 2020)
At the age of adolescence is a very rapid age and its development both in terms of psychological, physical, to the behavior of the section associated with puberty, so it is not accompanied by a good way it will become a health problem. This research was conducted based on the p-process theory which aims to determine the characteristics of respondents from adolescents in the Lontar PIK-R region, understand the level of knowledge, attitudes, and actions of the respondents related to health, discuss the media according to the respondents interests, look for media that is suitable for adolescents in Kampung KB Lontar area. The study was conducted by the observational method because the researcher did not provide any treatment to the respondents with a cross-sectional design. Based on the results of research and discussion that have been done, some things can be denied from respondents who already have knowledge about the health that is accountable but are not related to good judgment and actions.Keyword: adolescents, Kampung KB, PIK-R, reproductive health, behavior, p-process